Isolation and Antibiogram of Escherichia coli from Canine Pyometra in Puducherry Region - Vignesh, Manivasagam; Vasu, JayaLakshmi; Nivedha, Devanathan; Srinivas, Mouttou Vivek; Iyyanar, Shalini; Mukhopadhyay, Hirak Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Pyometra is a life-threatening and hormone induced cystic endometrial hyperplasia seen predominantly in older bitches, complicated with secondary bacterial infections. This study was performed with the objective of isolation and antibiogram of Escherichia coli from canine pyometra. Vaginal swabs were collected aseptically from 20 canine pyometra cases, presented to Veterinary Clinical Complex, Puducherry (India) for identification of E. coli isolates. Based on colony characters, microscopic observation, biochemical tests, 12 (60%)  E. coli isolates were identified. All the 12 phenotypically positive E. coli isolates were confirmed further by PCR using the primer targeting alr gene. E. coli isolates were found sensitive to Gentamicin (100%), Ceftriaxone (83%), Enrofloxacin (75%) and Ciprofloxacin (66%), but were resistant to commonly used antibiotics like Amoxyclav (100%), Ceftazidime (58%) and Cefotaxime (42%). The results provided an authentic and reliable information to choose an effective antibiotic to treat E. coli infection causing canine pyometra.
Keywords: Antibiogram; Canine; E. coli; Hormonal imbalance; Pyometra